Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Di PT Hutchison 3 Indonesia - Abadi Siregar, Mayer (Journal of Economics & Business UBS, 2020)
Quality of service to customers has a very important role. PT Hutchison Tri Indonesia which is engaged in telecommunication services, hence to improve the quality of management services form for 3Store, the application of the new concept is still not sure whether it can improve the quality of service or vice versa. With very different concepts raises the pros and cons of customers. The problem to be studied is